2020
DOI: 10.3390/w12082120
|View full text |Cite
|
Sign up to set email alerts
|

Urban Flood Modeling Using 2D Shallow-Water Equations in Ouagadougou, Burkina Faso

Abstract: Appropriate methods and tools accessibility for bi-dimensional flow simulation leads to their weak use for floods assessment and forecasting in West African countries, particularly in urban areas where huge losses of life and property are recorded. To mitigate flood risks or to elaborate flood adaptation strategies, there is a need for scientific information on flood events. This paper focuses on a numerical tool developed for urban inundation extent simulation due to extreme tropical rainfall in Ouagadougou c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The two river outlets (Figure 2b) located at the Hongwanchong and Qianshan River and two typical pipes (Figure 2a) in the study area were selected. The simulation results of the scalar flowrate time series (Figure 6) at the two basin outlets showed that the model had a high stability, and the flow processes of the two outlets were consistent with other similar studies [45,46]. The typical pipe discharge was also evaluated (Figure 7).…”
Section: Model Rationality Verificationsupporting
confidence: 84%
“…The two river outlets (Figure 2b) located at the Hongwanchong and Qianshan River and two typical pipes (Figure 2a) in the study area were selected. The simulation results of the scalar flowrate time series (Figure 6) at the two basin outlets showed that the model had a high stability, and the flow processes of the two outlets were consistent with other similar studies [45,46]. The typical pipe discharge was also evaluated (Figure 7).…”
Section: Model Rationality Verificationsupporting
confidence: 84%
“…However, monthly minimum and maximum temperatures varied from 11.1 to 22.4 °C and 33.7–43.1 °C respectively. The monthly relative humidity ranged between 29.91 and 86.71%, with an average of 55.98% ( Figure 3 ) Coulibaly et al. (2020) reported an average daily minimum and maximum temperature of 16 and 40 °C respectively, and a relatively lower mean annual precipitation of 788 mm Ibrahim et al.…”
Section: Resultsmentioning
confidence: 99%
“…Hydraulic models are mathematical models that replicate water movements by solving equations derived from conservation laws of mass, energy, and momentum (Coulibaly et al, 2020). All hydraulic models are sensitive to geometric and physical descriptions of the river, such as number of cross‐sections, spacing between cross‐sections, bottom slope, bathymetric point data, quality of the mesh, model parameters (Manning's n), and the structural type of model (i.e., 1D, 2D or 3D).…”
Section: Methodsmentioning
confidence: 99%